2012
DOI: 10.4269/ajtmh.2012.12-0078
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Community Management of Fever (Using Antimalarials With or Without Antibiotics) on Childhood Mortality: A Cluster-Randomized Controlled Trial in Ghana

Abstract: Malaria and pneumonia are leading causes of childhood mortality. Home Management of fever as Malaria (HMM) enables presumptive treatment with antimalarial drugs but excludes pneumonia. We aimed to evaluate the impact of adding an antibiotic, amoxicillin (AMX) to an antimalarial, artesunate amodiaquine (AAQ+AMX) for treating fever among children 2–59 months of age within the HMM strategy on all-cause mortality. In a stepped-wedge cluster-randomized, open trial, children 2–59 months of age with fever treated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
54
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 37 publications
0
54
0
Order By: Relevance
“…Will iCCM encourage drug 'overtreatment', resulting in drug resistance? Addition of rapid diagnostic testing to iCCM (proven feasible elsewhere in Uganda and sub-Saharan Africa) 20,29,39 should be seriously considered.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Will iCCM encourage drug 'overtreatment', resulting in drug resistance? Addition of rapid diagnostic testing to iCCM (proven feasible elsewhere in Uganda and sub-Saharan Africa) 20,29,39 should be seriously considered.…”
Section: Discussionmentioning
confidence: 99%
“…20 In a multi-methods Ethiopian study, volunteer CHWs treating diarrhoea, pneumonia, and fever and were highly accessed by community members 22 . Our study is complimentary suggesting multi-illness iCCM using CHWs with variable formal education is feasible, which is supportive of work in Eastern Uganda 23,[27][28][29][30] ; however, caution is needed to further understand quality of work, an issue highlighted by a recent study from Central Uganda.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, other research has shown that many iCCM programs have not achieved decreases in mortality and fail to perform on intermediate outcomes. [13][14][15][16] Especially, troubling is the result of a study in which adding pneumonia management to an existing program of diarrhea and malaria community management led to no statistically significant reduction in mortality in a well-controlled randomized controlled trial. 15 Therefore, it is imperative to perform research that assesses the efficacy and acceptability of iCCM programs.…”
Section: Introductionmentioning
confidence: 99%
“…The traditional domain of SMW is the healthcare industry, where waste is generated from a variety of healthcare activities. However, a limited variety of healthcare activities can also occur in households such as being found in home based care [3] [4], shortened hospital stay [5], care and treatment of chronic diseases in aging populations [6], and home management of illnesses such as malaria [7]. Although SMW constitutes up to 0.1% of the mixed municipal solid waste stream, its hazardous character attracts public sensitivity and poses a challenge to health and municipal authorities [8].…”
Section: Introductionmentioning
confidence: 99%